1998
DOI: 10.1046/j.1365-2648.1998.00493.x
|View full text |Cite
|
Sign up to set email alerts
|

Are children given insufficient pain‐relieving medication postoperatively?

Abstract: The literature often suggests and assumes that children are under-medicated postoperatively. A review of the literature leads to the conclusion that only a few studies answer the question of whether children's pain is relieved insufficiently. The lack of consensus on expected pain intensity after surgery and caution about prescribing analgesics could explain why analgesics are often prescribed on a pro re nata (prn) basis. Prescription on a prn basis, in fact, means that the nurse makes the decision whether or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
50
1
2

Year Published

2004
2004
2011
2011

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 59 publications
(53 citation statements)
references
References 24 publications
0
50
1
2
Order By: Relevance
“…In spite of the maximal doses prescribed to both TT/TE children in the present study, only a mean of about 60% of paracetamol and diclophenac were given during the first 24 h. Paracetamol and diclophenac were to be ''administered at regular intervals'' following standard prescription, and not on a pro re nata (prn) basis as recommended by Hamers et al [10]. There was also an ordination of morphine i.v.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…In spite of the maximal doses prescribed to both TT/TE children in the present study, only a mean of about 60% of paracetamol and diclophenac were given during the first 24 h. Paracetamol and diclophenac were to be ''administered at regular intervals'' following standard prescription, and not on a pro re nata (prn) basis as recommended by Hamers et al [10]. There was also an ordination of morphine i.v.…”
Section: Discussionmentioning
confidence: 88%
“…The experience and attitudes of the observer/ nurses are important [10,30], but the patient/ child's experience of pain is subjective and his/ her experience has to be regarded as the correct one. Therefore, the scoring of a lower pain level by staff than by children and parents must be a real underestimation that might have resulted in inadequate pain management.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These data support the need for pain medication titration and validate that the amount required to relieve pain differs from child to child. 5,6,8 A common side effect of all opioids is nausea and vomiting. Unfortunately, almost 30% of the patients had nausea or vomiting, which is consistent with the literature for patients after T&A.…”
Section: Discussionmentioning
confidence: 99%
“…6 Pain researchers have traditionally concluded that children are routinely undermedicated for pain when they receive less analgesic than ordered. 7,8 Additional research is warranted to determine if commonly prescribed analgesics can be administered by postanesthesia nurses to effectively relieve pain and improve patient outcomes after T&A.…”
mentioning
confidence: 99%